Method for coating the surface of a structure and the structure

JP7641669B2Active Publication Date: 2025-03-07株式会社コスモテクノロジー
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024007706
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2025-03-07
Estimated Expiration
2042-06-16

Smart Images

  • Figure 0007641669000014
    Figure 0007641669000014
  • Figure 0007641669000015
    Figure 0007641669000015
  • Figure 0007641669000016
    Figure 0007641669000016
Patent Text Reader

Abstract

To provide a method of coating the surface of a structure made of stones such as concrete and porcelain tiles, various metals, resins, etc., and constructed in the ocean, the method making it possible to visually recognize the state of the surface of the structure from the outside, reinforce the surface of the structure, and prolong the effect of preventing the contamination and deterioration of the surface of the structure, and provide such a structure.SOLUTION: The method includes: a step 3 of applying a transparent polyurea 12, which is a resinous compound based on a urea-bond formed by a chemical reaction between an isocyanate and a polyamine, to a front 11a of a structure 10a constructed in the ocean; and a step 4a of applying a coating material 14, which is obtained by using a silicon polymer-based antifouling coating material as a base agent and adding an organic antibacterial agent and an inorganic antibacterial agent as additives to the base agent, to the polyurea 12.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for coating the surface of marine structures made of concrete, various metals, resins, etc., and to such structures. [Background technology]

[0002] Conventionally, for example, Japanese Patent Application Laid-Open No. 2010-1707 (Patent Document 1) has proposed a reinforced coating method that allows the surface condition of the base material of a concrete structure to be visually confirmed from the outside. The conventional example in Patent Document 1 involves removing dirt from the surface of a concrete structure, applying a transparent polyurethane resin solution to the surface of the concrete structure, then adhering a continuous glass fiber sheet, applying the transparent polyurethane resin solution on top of that to impregnate the continuous glass fiber sheet, and drying and solidifying the solution to form a transparent or translucent first coating layer.

[0003] Furthermore, JP 2011-169085 A (Patent Document 2) proposes a reinforced coating method for the surface of a concrete structure that realizes a reinforced coating that allows the surface condition of the base material of the concrete structure to be visually confirmed from the outside, a reinforced coating structure for a concrete structure, and a reinforced concrete structure. The conventional example of Patent Document 2 is a glass continuous fiber sheet in which glass fiber threads are arranged so that a maximum of two threads cross at the same location, which is attached to a structure 2 via a transparent polyurethane resin, and then a transparent polyurethane resin is applied on top of the glass continuous fiber sheet to impregnate the sheet, which is then dried and solidified to form a transparent or translucent coating layer.

[0004] Furthermore, JP 2016-180229 A (Patent Document 3) proposes a concrete coating structure and a concrete surface coating method that allows damaged areas to be visually confirmed when conducting inspections, reduces the workload of workers, and does not cause anxiety to users. In the conventional example of Patent Document 3, the coating structure comprises a base layer applied to the concrete surface, a continuous glass fiber sheet layer formed by application to the base layer, an intermediate resin layer applied on the continuous glass fiber sheet layer, and a surface layer applied on the intermediate resin layer, and transparent polyurethane resin is used for the base layer, intermediate resin layer and surface layer, and the microcapsules consist of an outer shell which is a liquid-tight hollow sphere and a liquid fluorescent substance enclosed within the outer shell which emits light when irradiated with excitation light, and are added in a predetermined amount to a coating agent of transparent polyurethane resin and then kneaded, and are in a dispersed state in the coating film after the transparent polyurethane resin has dried. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-1707 A

[0006] [Patent Document 2] JP 2011-169085 A

[0007] [Patent Document 3] JP 2016-180229 A Summary of the Invention

[0008] The present invention provides a method for coating the surface of a structure which is installed in the ocean and is made of concrete, porcelain tiles and other stone materials, various metals, resins, etc., and which enables the surface condition of the structure to be visually confirmed from the outside, strengthens the surface of the structure, and extends the life of the effect of preventing the surface of the structure from becoming dirty and deteriorating, and also provides the structure itself.

[0009]

[0010]

[0011] The present invention is a method for coating the surface of a structure located in the ocean, comprising the steps of: cleaning the surface of the structure; providing protection to the surface of the structure; applying transparent polyurea, which is a resin compound based on urea bonds produced by a chemical reaction between isocyanate and polyamine, to the surface of the structure; applying a paint having a silicon polymer-based antifouling paint as a base agent to which an organic antibacterial agent and an inorganic antibacterial agent are added as additives, to the applied transparent polyurea; and removing the protection and cleaning the surface.

[0012] Furthermore, the present invention relates to a structure characterized in that a transparent polyurea, which is a resin compound based on urea bonds produced by a chemical reaction between isocyanate and polyamine, is applied to the surface, and a paint having a silicon polymer base agent to which an organic antibacterial agent and an inorganic antibacterial agent are added as additives is applied to the applied transparent polyurea, and the structure is installed in the ocean.

[0013] The present invention makes it possible to visually check from the outside the state of deterioration of the surfaces of marine structures made of concrete, ceramic tiles, various metals, resins, etc., and has the effect of strengthening the surfaces of the structures, preventing contamination of the surfaces of the structures, and providing long-term inspectability. [Brief description of the drawings]

[0014] [Figure 1] 1 is a process explanatory diagram of this embodiment for a structure installed in the ocean, and FIG. 2 is a process explanatory diagram of this reference example for a structure installed on land. [Diagram 2] FIG. 1 is a configuration diagram of a present reference example of a structure provided on land. [Diagram 3] FIG. 1 is a configuration diagram of an embodiment of a structure installed in the ocean. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, a reference example of the present invention will be described with reference to the accompanying drawings. A method for coating a surface 11 of a structure 10 made of concrete or the like and installed on land as shown in FIG. 2 will be described with reference to FIG. The first step 1 of this embodiment is a step of cleaning a surface 11 of a structure 10 provided on land. High-pressure washing and blasting are used to remove dirt, laitance, lifting, and deteriorated areas from the surface, remove metal rust, and clean the surface 11.

[0016] The next step 2 is a step of curing the surface 11 of the structure 10. Scattering is prevented by covering the processing area of ​​the surface 11. Covering the boundary area of ​​the processing area of ​​the surface 11 with masking tape makes it easier to remove the covering.

[0017] Next, step 3 shown in FIG. 1 is a step of applying transparent polyurea 12, which is a resin compound based on urea bonds produced by a chemical reaction between isocyanate and polyamine, to surface 11 of structure 10 shown in FIG. 2. Depending on the condition of the object surface, apply a primer if necessary. Apply the specified amount of Polyurea 12 with a brush, roller, or airless sprayer. Check the amount of Polyurea 12 used by checking the machine counter and the film thickness of the sample. The standard application amount of Polyurea 12 is 0.5 to 1.0 kg / m2, and the drying time between coats is approximately 24 hours. It forms a tough coating that ensures visibility of the structure's surface for a long period of time, over 15 years. Unlike normal paint films, it is less likely to break even when subjected to physical damage from external sources such as friction or impact. Polyurea 12 is composed of 50-75% hexamethylene-1,6 diisocyanate homopolymer, 5-30% glutaric acid, 2 methyl-dimethyl ester, 1-25% hexamethylene diisocyanate oligomer, and 0.1-0.5% hexamethylene diisocyanate. Other polyurea 12 consists of tetraethyl lead, methylenecyclohexane, aspartic acid 75-95% and oxydipropanol benzoic acid ester 1-5%.

[0018] Polyurea 12 is a resin compound based on urea bonds produced by the chemical reaction of isocyanate and polyamine, and has excellent waterproofing, chemical resistance, abrasion resistance, heat resistance, and corrosion resistance. Its quick-drying property, which means it hardens in just a few seconds to a few minutes, allows it to be used in a variety of situations and expands the range of applications it can be used in. Some grades have an elongation rate of over 400%, and the strength that comes from that flexibility is why it is used, for example, as an explosion-proofing measure for military facilities. Since it does not contain solvents, it has no adverse effects on the environment and can easily produce a surface coating that strengthens the surface of a structure.

[0019] Polyurea 12 has extremely excellent physical properties such as chemical resistance and corrosion resistance compared to conventional polyurethanes. Depending on the grade, it has long-term resistance to 50% sulfuric acid, so it protects the surface of structures from corrosion caused by strong chemicals such as acids and strong alkalis for a long period of time. In addition, in the JIS standard paint abrasion test, the amount of paint film worn off after the test was 3 mg, demonstrating overwhelming abrasion resistance compared to other conventional polyurethane systems. It has extremely high weather resistance and can protect the surface of structures for long periods of time even in harsh outdoor environments.

[0020] Polyurea 12 has excellent strength and flexibility, with a surface strength equivalent to that of concrete, and some grades have an elongation rate of over 400%. Its strength, combined with its toughness and flexibility, makes it suitable for use as an explosion-proofing measure for military facilities. In particular, it fits into cracks in concrete substrates without cracking, and is effective in protecting the substrate. As described above, Polyurea 12 has excellent characteristics such as waterproofness, chemical resistance, abrasion resistance, rust prevention, peeling prevention, explosion resistance, heat resistance, impact resistance, and UV resistance.

[0021] The process in this reference example is a method in which 100% pure polyurea resin, mainly hybrid polyurea resin, is sprayed onto the surface at high temperature and pressure in order to improve the durability and extend the life of the structure. There are three types of resins: aromatic, aliphatic, and aspartic acid ester, and they all have excellent weather resistance. Its super-fast drying feature means that it has excellent workability, even when sprayed on vertical surfaces or ceilings, without dripping. The extremely strong "urea bond" provides excellent resistance to salt, acids, alkalis, and other chemicals. Excellent adhesion allows for a seamless coating that reinforces the area to which it is applied. Its excellent durability and ease of installation make it possible to reduce life cycle costs.

[0022] Materials that have conventionally been used as coating materials for the surfaces of structures include epoxy resins and polyurethanes. Epoxy resins generally have excellent adhesive properties and chemical resistance, but are poor at crack conformability. Polyurethane is soft and has excellent crack adaptability, but it is poor in chemical resistance, such as resistance to alkaline chemicals, and weather resistance. Compared to conventional epoxy resins or polyurethanes, polyurea has excellent chemical resistance, weather resistance, and crack adaptability. These excellent physical properties are due to the "urea bond" of polyurea, which provides high rigidity and excellent substance barrier properties while maintaining flexibility.

[0023] The chemical formulas of polyurethane and polyurea 12 are shown below. The reaction product of polyols and isocyanates in polyurethane is shown in Equation 1 below. [ka]

[0024] The reaction product of amines and isocyanates in polyurea 12 is shown below in Equation 2. [ka]

[0025] Representative physical properties of Polyurea 12 are shown in Table 1 below. [Table 1]

[0026] Detailed physical properties of Polyurea 12 are shown in Table 2 below. [Table 2]

[0027] The physical properties of the Polyurea 12 coating are shown in Table 3 below. [Table 3]

[0028] Conventional polyurethanes are based on the exothermic reaction of MDI (diphenylmethane diisocyanate) with polyisocyanates, resulting in compounds with hydroxyl end groups such as polyols. Polyurea 12 is based on the same exothermic reaction of MDI (diphenylmethane diisocyanate) and polyisocyanate as polyurethanes, but the key difference is that Polyurea 12 utilizes active hydrogen groups (amines). Polyurea 12 solves the problems of conventional polyurethanes, such as the possibility of poor curing in moisture or high humidity environments, and low impact resistance and heat resistance, and improves surface properties. The C-N bonds in the structure of polyurea 12 are stronger than the C-O bonds in the structure of polyurethane, resulting in polyurea having higher heat resistance, resistance to thermal deformation, elasticity and toughness, thereby improving the ability to adapt to substrate movement and cracking.

[0029] Pure Polyurea 12 is 100% hydrophobic and will not be inhibited by the presence of moisture. For example, it will cure as a film even on a water surface and strength development will not be impaired. In addition, after the curing reaction, the coating performance can be maintained for a long period of time without being affected by water or ultraviolet light. In contrast, polyurethane is very sensitive to moisture, which deteriorates the curing property and strength of the coating film. After the curing reaction, the polyurethane-coated substrate must be periodically re-treated to prevent degradation by ultraviolet light. Polyurethane may also be permanently hydrolyzed when exposed to moisture.

[0030] Polyurea 12 is applied using a brush, roller, or airless sprayer. Apply the specified amount using a high-temperature, high-pressure spray machine or the recommended roller. Check the amount used by checking the machine's counter and the film thickness of the sample. The standard method for applying Polyurea 12 is to heat and mix agents A and B in a dedicated spray truck and then spray the material using a high-temperature, high-pressure spray machine. The transparent polyurethane 12 used in this reference example can be used to obtain a stable coating by application with a general paint roller without using such spray equipment.

[0031] Next, step 4 of this reference example shown in FIG. 1 is a step of applying an inorganic glassy coating agent 13 to the applied transparent polyurethane 12 . The main component constituting the inorganic glassy coating agent 13 is shown in Chemical Formula 3 below. [ka]

[0032] The hardener constituting the inorganic glassy coating agent 13 is shown below. M(OR)n M = metal element such as tin When moisture in the air is added to the hardener constituting the inorganic glassy coating agent 13, the following chemical reaction occurs. M(OR)n +nHO → M(OH)x +nROH(alcohol)

[0033] When a curing agent and moisture in the air are added to the main agent constituting the inorganic glassy coating agent 13, a chemical substance shown in the following chemical formula 4 is produced. [ka]

[0034] The inorganic glassy coating agent 13 hardens by the reaction mechanism described above to form an organic-inorganic composite coating film having polysiloxane bonds. Polysiloxane is a silicone that contains a silicon-oxygen skeleton (Si-O bond) and organic groups such as methyl, ethyl, and phenyl groups. After the coating material hardens, the proportion of organic groups in the film components is extremely low, at just a few percent, and the structure is similar to that of inorganic materials such as quartz glass. Therefore, it has high hardness and weather resistance, and with a surface free energy (surface tension) of 20 mN / m or less, it has excellent water- and oil-repellency and release properties, and therefore exhibits extremely excellent stain-resistant properties and stain recovery properties over a long period of time. Therefore, the inorganic glassy coating agent 13 has a long-term repeatable cleaning recoverability of 15 to 20 years or more, and therefore can provide the structure surface with a long-term repeatable cleaning recoverability of exhaust gas and other oils, dirt, dust, sludge, etc., and ensure long-term inspectability.

[0035] Inorganic glass coating agent 13 has high weather resistance and provides antifouling and reusable cleaning properties to the surface of structures for a long period of time (over 15 years). It also has very high release properties against lacquer sprays and exhaust gases. The inorganic glassy coating agent 13 is composed of 90-99% silicone resin and 1-5% isopropyl alcohol as a base agent, and has 30-40% dibutyltin diacetate, 20-30% ethyl acetoacetate, 20-30% ethanol, 20-30% naphtha, petroleum, light alkylate, and 10-20% tetra-n-butoxy titanium as a hardening agent. The physical property data of the inorganic glassy coating agent 13 is shown in Table 4. [Table 4]

[0036] The physical property data of the coating film of the inorganic glassy coating agent 13 is shown in Table 5. [Table 5]

[0037] Inorganic glassy coating agents 13 are used in many public and private construction projects, such as preventing graffiti and posters, interior decoration of tunnels on expressways (visual guidance works), and protection of exposed concrete surfaces. The inorganic glass coating agent 13 can be made glossy, semi-glossy, or matte by mixing silica glass powder, and can also protect the design of the object to which it is applied. It can be applied directly to a variety of objects, but a primer may be applied if necessary depending on the type of substrate to be coated and the conditions. In addition, by mixing nanotechnology dispersions, which are a water-repellent fluororesin surface modification technology, depending on the purpose of the surface film's functionality, it is possible to obtain ultra-water-repellent films with a contact angle with water droplets of over 150°.

[0038] Since the inorganic glass coating agent 13 contains a very high proportion of inorganic matter, the coating film may crack if exposed outdoors for a long period of time. In order to prevent cracking without losing the transparency of the coating, the coating should be applied as thin as possible. Therefore, the standard coating amount is set at 0.04kg / m2, and it is necessary to apply it in a stretched manner. In addition, there is a method of dispersing and mixing bionanofibers such as cellulose nanofibers and chitin nanofibers derived from natural components, synthetic carbon nanotubes, or various nanofibers by electrospinning.

[0039] Furthermore, when chitin nanofibers are used, a dispersion of chitin nanofibers obtained by the manufacturing method described below is used. This method for producing chitin nanofibers is characterized by subjecting chitin-containing material derived from crustaceans to at least one deproteinization step and at least one decalcification step, a step of treatment with an acidic reagent, and then a defibration step. Furthermore, the method for producing chitosan nanofibers is characterized in that the chitin-containing material derived from crustaceans is subjected to at least one deproteinization step, at least one demineralization step, and at least one deacetylation step, and then subjected to a fiber defibration step (Patent Publication No. 5186694).

[0040] The final step 5 is to remove the protective covering and clean the surface, completing the process of this example.

[0041] The structure 10 of this reference example has a surface 11 coated with transparent polyurea 12, which is a resin compound based on urea bonds generated by a chemical reaction between isocyanate and polyamine, and then an inorganic glassy coating agent 13 is applied to the transparent polyurea 12, and the structure is installed on land. The structure 10 constructed on land is a structure such as a tunnel, a bridge pier, a girder, a pool, a dam, a food processing plant, a power plant, a pipeline, a waterway, a tank, a warehouse, a ship, a parking lot, a retaining wall, an industrial waste landfill, etc., and is made of one or more of concrete, stone materials such as porcelain tiles, metal, and synthetic resin.

[0042] The transparent polyurethane 12 applied is coated with an inorganic glassy coating agent 13, and the structure 10 of this reference example is installed on land. The performance of the structure 10 in the official confirmation test is shown in Table 6. A transparent coating film was formed on the surface 11 of the structure 10, which is strong, has a recovery effect that allows contaminants to be repeatedly cleaned off over a long period of time (over 15 years), and provides long-term inspectability. [Table 6]

[0043] Next, a method for coating a surface 11a of a structure 10a made of concrete or the like and installed in the ocean, which is an embodiment of the present invention shown in FIG. 3, will be described with reference to FIG. Most of the steps 1, 2, 3, and 5 are common to the method of coating a surface 11 of a structure 10 made of concrete or the like on land shown in FIG. 2, but step 4a shown in FIG. 1 is different. Step 4a shown in FIG. 1 is a step of applying paint 14, which uses a silicon polymer-based antifouling paint as a base agent and has an organic antibacterial agent and an inorganic antibacterial agent added as additives, to the applied transparent polyurea 12 on the surface 11a of the structure 10a as shown in FIG. 3.

[0044] Paint 14 is a marine paint with a special antibacterial treatment. By applying paint 14 to the surface 11a of a structure 10a, from large to small areas, using a silicon polymer-based antifouling paint as a base agent to which an organic antibacterial agent and an inorganic antibacterial agent are added as additives, it is possible to prevent marine organisms such as seaweed and shells from adhering to the applied area. This effect lasts for about 2 to 3 years, and long-term inspectability of surface 11a of structure 10a can be maintained with just simple cleaning. Over the course of about 2 to 3 years, the coating of paint 14 on surface 11a gradually dissolves together with the seawater. The presence of a transparent layer of polyurea 12 underneath allows for easy visual inspection of surface 11a of structure 10a.

[0045] By applying the paint 14, the surface 11a of the structure 10a is provided with a strong antifouling property, that is, a property to prevent adhesion of marine organisms, which lasts for a long period in the sea under stationary conditions. By repainting the paint 14 or attaching a sheet-like building material coated with the paint 14 during regular inspections every two to three years, the ease of inspecting the deterioration state of the surface 11a of the structure 10a is improved. The base agent that constitutes paint 14 is composed of 0.1-1% tetraethoxysilane, 1-5% copper pyrithione, 40-45% cuprous oxide, 1-5% zinc oxide, 1-5% red iron oxide, 1-5% petroleum naphtha G, 10-20% xylene, 10-20% ethylbenzene, 1-2% 1,2,4 trimethylbenzene, 0.1-1% 1,3,5 trimethylbenzene, 0.5-1% methyl alcohol, 0.5-1% ethyl alcohol, and other organic pigments and auxiliaries. The additives that make up Paint 14 are an organic-inorganic composite antibacterial agent / chitosan nanofiber solution, consisting of 0.1-2% 2-(thiocyanatomethylthio)-1,3-benzothiazole, 80-90% nanosilver aqueous solution (10,000 ppm), 10-20% chitosan nanofiber aqueous solution, and auxiliary agents. The physical property data of Paint 14, which uses a silicon polymer-based antifouling paint as a base agent and adds an organic antibacterial agent and an inorganic antibacterial agent as additives to the base agent, is shown in Table 7. [Table 7]

[0046] The physical property data of the coating film of Paint 14, which uses a silicon polymer-based antifouling paint as a base agent and adds an organic antibacterial agent and an inorganic antibacterial agent to the base agent as additives, is shown in Table 8. [Table 8]

[0047] The inspection cycle for the structure 10a installed in the ocean, such as a power plant, is about every 2 to 3 years. For this inspection, seawater is drained and the structure 10a is inspected and repaired. If deterioration of the structure 10a occurs, appropriate repair work is carried out and the paint 14 is reapplied on top of it. Alternatively, it is also possible to attach a sheet-like material to which the paint 14 has been applied elsewhere. Conventionally, there has been no surface treatment technology that can prevent the attachment of marine organisms when immersed in seawater under stationary conditions. In the past, toxic substances such as tributyltin (TBT) were sometimes mixed into the water to prevent shellfish from attaching to it, but this has now been completely banned by international treaty. Since then, technological development has progressed in the use of silicon polymer-based antifouling paints for the bottoms of ships such as tankers. However, the theory behind this is that the surface coating is gradually dissolved and renewed by the resistance of flowing water and navigation, thereby preventing the attachment of marine organisms, and this has created a problem in that it is difficult to achieve an effect of preventing the adhesion of marine organisms to the surface of marine structures in stationary conditions other than on ships. The paint 14, which uses a silicon polymer-based antifouling paint as a base agent to which organic and inorganic antibacterial agents are added as additives, is non-polluting and has passed official waste standard tests, yet is capable of providing highly durable anti-fouling properties over the long term to the surface of marine structures under stationary conditions. The same effect can be achieved in overseas waters other than Japanese waters.

[0048] Land tunnels are mainly divided into urban tunnels and mountain tunnels, each of which has different pollutants. The interior space of urban tunnels is polluted by exhaust fumes from the large volume of vehicle traffic, and in mountain tunnels, mud, sand, and calcium chloride deicing agent used in cold climates mix together, causing them to harden and adhere to each other. On the other hand, the structure 10a installed in the ocean is, for example, a tunnel structure located underwater, such as a power plant water intake. Because these structures are constantly in contact with seawater, large amounts of fungi, seaweed, and shells grow on them at a rate incomparable to that on land, covering the surface 11a of the structure 10a and significantly impeding its ease of inspection. By applying paint 14 to the applied transparent polyurethane 12 as shown in FIG. 3, it is possible to prevent exhaust gas and other oils, dirt, dust, sludge, fungi, seaweed, and shells from adhering to the surface of the structure and significantly impairing inspectability, thereby ensuring the inspectability of the surface of the structure for a long period of time.

[0049] The paint 14, which uses a silicon polymer-based antifouling paint as a base agent and has an organic antibacterial agent and an inorganic antibacterial agent added to the base agent, is a paint that does not contain organotin compounds (TBT). The attachment and proliferation of barnacles, mussels, and seaweed can sometimes completely cover the surface of marine structures, significantly reducing the ability to inspect the structure's surface. Furthermore, when a ship is in operation, marine organisms attach to and multiply on the ship's bottom while it is anchored, increasing the frictional resistance of the ship's bottom surface when it begins to move forward, resulting in economic losses such as increased fuel consumption. In order to avoid economic losses caused by such fouling of marine organisms, techniques for preventing the fouling of marine organisms have been developed in the past by mixing antifouling agents into paints and the like.

[0050] Conventional antifouling agents have mainly been organotin compounds (TBT), but against the backdrop of increased international awareness of environmental issues in recent years, there have been concerns that TBT could cause marine pollution and that TBT could be concentrated and accumulated in the bodies of fish and shellfish when it is discharged into seawater, and that this could have adverse effects on the human body if ingested. For this reason, the IMO (International Maritime Organization) adopted the AFS Convention (international treaty) in 2001, which led to a ban on the use of antifouling paints containing organotin compounds (TBT) from 2003 onwards. Due to this trend, it has become impossible to use certain toxic substances in marine organism adhesion prevention technology, and so silicon polymer-based antifouling paints, in which the surface coating of the ship's bottom is hydrolyzed and renewed by the flow speed of seawater and the resistance force during navigation, have been developed and widely used. However, because this type of paint prevents marine organisms from attaching due to the flow speed of seawater and the resistance force during navigation, there is a problem that it is difficult to prevent marine organisms from attaching to the surface of marine structures other than ships. Therefore, we used paint 14, which uses a silicon polymer-based antifouling paint as the base agent and adds organic and inorganic antibacterial agents to the base agent as additives, to create a paint that can prevent marine organisms from attaching to the ship for a long period of time even under stationary conditions.

[0051] Paint 14 uses a silicon polymer-based antifouling paint as a base agent to which organic and inorganic antibacterial agents are added as additives. Through the hydrolysis mechanism shown in chemical formula 5 below, the surface coating on the bottom of the ship gradually dissolves due to the resistance of seawater and the ship's movement while the ship is sailing, and the coating surface is constantly renewed, thereby maintaining the effect of preventing the attachment of marine organisms. These paints are commonly used on the bottoms of tankers, etc. [ka]

[0052] Paint 14, which uses a silicon polymer-based antifouling paint as a base agent to which organic and inorganic antibacterial agents are added as additives, does not cause environmental impacts such as marine pollution and is currently in wide use, but its effectiveness in preventing adhesion of marine organisms depends on the hydrolysis effect caused by the resistance force of seawater flow velocity. For this reason, the surfaces of underwater stationary structures such as marine structures other than the bottom of a ship are not subjected to the resistance caused by navigation, making it difficult to prevent the adhesion of marine life in a stationary state. However, this embodiment contributes to ensuring the long-term inspectability of the surfaces of underwater tunnel structures, such as the walls of power plant water intakes.

[0053] Paint 14, which uses a silicon polymer-based antifouling paint as a base agent to which organic and inorganic antibacterial agents are added as additives, maintains its effectiveness in preventing the adhesion of marine organisms for about 2 to 3 years even under stationary conditions in the ocean for the following reasons. The cause of marine biofouling is nutrients on the surface of the target object, which are a membrane-like layer of clumps of bacteria (commonly known as a biofilm layer). The presence of abundant nutrients on the surface of the target object serves as a breeding ground for the growth of marine organism larvae, and as the larvae repeatedly grow and attach, a thick adhesion layer is formed, which promotes the adhesion of marine organisms. In order to prevent marine organisms from attaching to the surface of stationary marine structures, it is necessary to impart a long-term effect of inhibiting the attachment and growth of shellfish larvae or the adhesion and settlement of algae. For this purpose, a method of adding an "antibacterial agent" that is expected to exert a long-term adhesion and settlement inhibitory effect to a silicon polymer-based antifouling paint according to the following procedure can be used. To achieve this, the following procedure is used to impart long-term antibacterial properties to silicon polymer-based antifouling paints.

[0054] There are two types of antibacterial agents: organic and inorganic. Organic antibacterial agents were originally used as medicines (detergents), and in a broad sense, antibiotics, anticancer drugs, and oxidizing agents (hydrogen peroxide, sodium hypochlorite) are also included in this category. Their characteristics include: 1. They are known to be relatively safe, 2. Many of them have low thermal stability and are not suitable for processing, 3. Many of them have a narrow antibacterial spectrum (the range of microorganisms that can be killed), and 4. They are prone to the emergence of resistant bacteria (fast-acting). Depending on their chemical structure, they can be classified into 19 types, including alcohols, phenols, esters, peroxides / epoxy, halogens, imidazole / thiazoles, thiocarbamate, surfactants, and organometallics. So-called "antibacterial agents" that inhibit the attachment of shellfish larvae and marine algae, or inhibit the growth of microorganisms such as bacteria and mold, can be broadly divided into organic antibacterial agents and inorganic antibacterial agents. Organic antibacterial agents are further divided into synthetic organic antibacterial agents and natural organic antibacterial agents. Synthetic organic antibacterial agents include alcohols, phenols, aldehydes, carboxylic acids, esters, ethers, nitriles, halogens, pyridine-quinolines, triazines, isothiazolinones, imidazole-thiazoles, anilides, biguanides, disulfides, thiocarbamates, quaternary ammonium salts, amphoteric surfactants, and organometallics. Natural organic antibacterial agents include hinokitiol, hiba oil, mugwort extract, eucalyptus extract, peppermint oil, camphor, limonene, mustard extract, natural wasabi components, catechin (green tea extract), persimmon extract, shiso extract, bamboo extract, chitosan (chitosan nanofiber), polylysine, and natural antibiotics. On the other hand, inorganic antibacterial agents are antibacterial agents whose main composition is inorganic compounds, and are currently the most widely used. Inorganic antibacterial agents include antibacterial metal-supported groups (silicate, phosphate, oxide, glass), metal (hydr)oxide groups (zinc oxide, calcium (hydr)oxide), metallic silver groups (nanosilver, silver colloid), and photocatalyst groups (single type (titanium dioxide), hybrid type (titanium dioxide + silver, copper-supported)).

[0055] The characteristics of organic antibacterial agents are as follows: Antibacterial: Immediately effective, but only certain types are effective Heat resistance: Generally, some of the resin will evaporate or decompose at the resin molding temperature. Durability: Easily evaporated or decomposed by water, heat, etc., resulting in reduced effectiveness. Processability: If heat is applied during processing, there is a risk of evaporation or dispersion. Safety: The toxicity of the antibacterial agent itself is low, but the safety of the agent has not been completely confirmed. There are also.

[0056] The characteristics of inorganic antibacterial agents are as follows: Antibacterial: Slow-acting and effective against a wide range of bacteria, mold and yeast. Heat resistance: No decomposition or deterioration even at resin molding temperatures (maximum 350°C). Durability: It is not eluted by organic solvents, etc., and maintains antibacterial properties for a long period of time. Workability: In powder form, it can be handled in the same way as conventional pigments. Safety: Most products contain silver as an active ingredient, and silver is highly safe. Inorganic antibacterial agents are metallic antibacterial solutions, typically containing silver. Silver has been a part of human society since ancient times and is used in tableware such as knives, forks, and plates. Nowadays, with the development of nanotechnology (ultrafine processing technology), nanosilver antibacterial solution is readily available.

[0057] Of these, it is preferable to extract at least two types from aqueous solutions of phenols, pyridine / quinolines, triazines, isothiazolones, and anilides, which have an inhibitory effect on microbial biosynthesis, and to extract at least one type from aqueous solutions of nitriles and imidazole / thiazoles, which have an inhibitory effect on the energy acquisition activity of microorganisms. In addition, the above organic antibacterial agent is mixed and stirred with a nanosilver antibacterial aqueous solution as an inorganic antibacterial agent. At this time, it is preferable to adjust the concentration of the aqueous solution so that the silver concentration is 10,000 ppm. As a mixing and stirring method, a method of extracting the mixture raw material powder using a vacuum stirring dryer is preferable.

[0058] The additive raw material obtained above is mixed and stirred with a chitosan nanofiber dispersion liquid, which is purified and dissolved in an isopropyl alcohol solvent to obtain a solvent-based dispersion liquid. In this case, as a guideline for the amount to be produced, the solution is prepared so that the additive is a 10% additive solution relative to the amount of the base agent, silicon polymer-based antifouling paint.

[0059] For example, if the amount of silicon polymer-based antifouling paint is 20 kg, the amount of additive solution to be mixed is set to 2 kg. By mixing the base agent, silicon polymer-based antifouling paint, with the long-term antibacterial additive solution obtained as described above as an additive, it is possible to form a surface film that does not cause marine fouling under stationary conditions in the ocean and exhibits long-term prevention of marine organism adhesion. Before application, an electric mixer is used to slowly mix the contents of the container over a period of time until the contents are uniform, and then the paint is applied to a clean, dry, and clean surface using a standard medium-pile paint roller or similar tool to finish the application.

[0060] The structure 10a of this embodiment has a surface 11a coated with transparent polyurea 12, which is a resin compound based on urea bonds generated by a chemical reaction between isocyanate and polyamine, and the coated transparent polyurea 12 is then coated with silicon polymer-based antifouling paint 14, and is installed in the ocean. The structures 10a installed in the ocean include structures such as tunnels, bridge piers, girders, pools, dams, food processing plants, power plants, pipelines, waterways, tanks, warehouses, ships, parking lots, retaining walls, and industrial waste landfills, and are made of one or more of concrete, stone materials such as porcelain tiles, metal, and synthetic resin.

Claims

1. cleaning a surface of a marine structure; A step of curing the surface of the structure; A step of applying a transparent polyurea, which is a resin compound based on urea bonds generated by a chemical reaction between isocyanate and polyamine, to the surface of the structure; A step of applying a paint having a silicon polymer-based antifouling paint as a base agent and an organic antibacterial agent and an inorganic antibacterial agent as additives to the base agent to the applied transparent polyurea; A step of removing the covering and cleaning; 1. A method for coating a surface of a structure, comprising the steps of:

2. A structure characterized in that a transparent polyurea, which is a resin compound based on urea bonds produced by a chemical reaction between isocyanate and polyamine, is applied to the surface, and a paint having a silicon polymer-based antifouling paint as a base agent to which an organic antibacterial agent and an inorganic antibacterial agent are added as additives is applied to the applied transparent polyurea, and the structure is installed in the ocean.

3. 2. The method for coating a surface of a structure according to claim 1, wherein the structure is made of at least one of concrete, metal, and synthetic resin.

Citation Information

Patent Citations

  • Anticorrosive coating method for projecting side of steel sheet pile

    JP1988171682A

  • Suppression of ocean contamination

    JP1989249707A

  • Reinforced coating method of concrete structure surface

    JP2010001707A

  • Reinforced coating method of concrete structure surface, reinforced coating structure of concrete structure, and reinforced coating structure

    JP2011169085A

  • Concrete piece exfoliation prevention structure, concrete exfoliation prevention method, and alicyclic polyamine used therefor

    JP2016030716A